Local buckling on large sandwich panels applied to light aviation: Experimental and computation dialogue. (15th April 2023) - Ginot, M.; Bouvet, C.; Castanié, B.; D'Ottavio, M.; Serra, J.; Mahuet, N.
Highlights: Large flat specimens are used to analyse wrinkling. Specimens were tested under Compression and shear on the multiaxial VERTEX Test bench. Experimental and computation dialogue is performed. The nonlinear FEM provides an improved, conservative prediction of wrinkling. Abstract: Wrinkling is a local buckling phenomenon in sandwich structures subjected to compression and shear loading that is challenging for the aircraft design engineer. Numerous wrinkling models are proposed in the literature but historical formulas developed after the Second World War are still widely used by the industry with important knock down factors. Theory-experiment correlation should be the final step in validating and evaluating the models. This article presents an experimental-computational dialogue on structural tests on large sandwich panels of dimensions 558 × 536 mm 2 representative of the design used in light aviation. The panels were subjected to compressive and shear loading by using the VERTEX test bench and wrinkling failures were observed. Comparisons are first made with linear wrinkling models. Despite correlations are quite encouraging, the imperfection-sensitivity of the experimentally observed wrinkling failure questions the pertinence of a linear bifurcation approach. A nonlinear Finite Element Model (FEM) of the sandwich panels is then developed. Initial imperfections measured by Stereo Digital Image Correlation (SDIC) are directly introduced in the mesh and an elastoplastic constitutive law for the core is implemented. Dynamic explicit computation is used to access the highly nonlinear behaviour and matches the test observations very well. The nonlinear FEM provides an improved, conservative prediction of wrinkling loads over the linear models.